Comparison of Memory usage between REST API in Javascript and Golang - Hafizd Ardiansyah; Agung Fatwanto (Universitas Bumigora, 2022)
Various mobile devices have limited memory, thus it must be used as effectively as possible. As a result, apps that will operate on mobile devices must take memory usage efficiency into account. The REST API, which is typically used to connect several applications that utilize different types of technology so that the applications can be connected, is one sort of technology that is currently commonly used to construct mobile applications. Javascript and Golang are the types of technology used to create the REST API. Undoubtedly, each of these technologies offers a unique performance. Research that can give a broad overview of the variations in the impact of memory resource utilization between Javascript and Golang is therefore required. In this work, two REST APIs are created using Javascript and Golang by researchers utilizing an experimental quantitative methodology. Following that, the memory utilization of the two REST APIs was evaluated using the exact same two types of datasets obtained from console.cloud.google.com. There was a difference in memory consumption between Javascript and Golang after the Wilcoxon test, t-test for paired data, and equivalence test, but the difference was essentially inconsequential (practically insignificant).